2012
DOI: 10.5194/esdd-3-827-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal analysis of the urban-rural gradient structure: an application in a Mediterranean mountainous landscape (Serra San Bruno, Italy)

Abstract: The most recent and significant transformations of European landscapes have occurred as a consequence of a series of diffused, varied and often connected phenomena: urban growth and sprawl, agricultural intensification in the most suitable areas and agricultural abandonment in marginal areas. These phenomena can affect dramatically ecosystems' structure and functioning, since certain modifications cause landscape fragmentation while others tend to increase homogeneity. Thus, a thorough comprehension of the evo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Sprawl phenomena show that anthropic expansion (Harris, 1984;Saunders et al, 1991;Forman, 2008) has led to a remarkable qualitative and quantitative reduction in rural areas (Modica et al, 2012) with consequent ecosystemic changes caused by the progressive isolation of the residual natural areas (MacArthur and Wilson, 1967;Boardman, 1981;Farhing and Merriam, 1985;Rodrigues et al, 2004;Hoekstra et al, 2005) and the interruption of the ecological connections existing between spatially separate landscape elements (EEA, 2011).…”
Section: Landscape Fragmentationmentioning
confidence: 99%
“…Sprawl phenomena show that anthropic expansion (Harris, 1984;Saunders et al, 1991;Forman, 2008) has led to a remarkable qualitative and quantitative reduction in rural areas (Modica et al, 2012) with consequent ecosystemic changes caused by the progressive isolation of the residual natural areas (MacArthur and Wilson, 1967;Boardman, 1981;Farhing and Merriam, 1985;Rodrigues et al, 2004;Hoekstra et al, 2005) and the interruption of the ecological connections existing between spatially separate landscape elements (EEA, 2011).…”
Section: Landscape Fragmentationmentioning
confidence: 99%
“…By analyzing times series satellite images and by referring to others studies [2,[17][18][19][20][21][22][23][24][25], we identified various factors that may influence the urban growth in the GBA. These factors can be divided into natural factors-i.e., altitude and slope-and human factors-i.e., the distance variable, indicating distances to certain elements, such as roadway infrastructure, demographic variables, indicating the influence of urban agglomeration, the total exploitation coefficient, as well as the impact of the population density in general.…”
Section: Variables Identificationmentioning
confidence: 99%
“…In the gradient view, the urban-rural dichotomy can be thought of as a landscape gradient, if considered as a sliding level of human influence from rural to urban landscape, including ecological processes, flows and movements of goods, energy, people, capital, and information (Modica et al, 2012). The urban-rural gradient approach is commonly used to investigate how urbanisation phenomena are changing the ecological patterns and related processes across the landscape (McDonnell and Pickett, 1990;Luck and Wu, 2002;Hahs and McDonnell, 2006;Yang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[Journal of Agricultural Engineering 2013; volume XLIV(s2):e91] sity indicators associated with geographic features (Torrens and Alberti, 2000;Vizzari, 2011a;Vizzari, 2011b;Modica et al, 2012).…”
Section: Introductionmentioning
confidence: 99%